Cruise traveling behavior post-COVID-19: an integrated model of health protection motivation, travel constraint and social learning - Yuen, Kum Fai (2022)
Travel restrictions have harmed the cruise industry as a result of the COVID-19 pandemic. The goal of this study, which is attributed to permanent changes in the regulatory and social landscape, is to identify and examine the factors influencing post-COVID-19 cruise travel intention. To explain cruise travel intention, we developed a theoretical model incorporating health protection motivation, social learning and travel constraint theories. An online survey was conducted with 400 valid responses collected from Singapore. The theoretical model was estimated using structural equation modeling and the survey data. The findings indicate that (1) observing societal behavior, (2) observing the COVID-19 situation, (3) threat appraisal, and (4) coping appraisal all have a direct influence on travel constraint negotiation. Furthermore, travel constraint negotiation and societal observation have a direct impact on intention. An intriguing finding is that observing the COVID-19 situation has no effect on threat assessment, which can be attributed to pandemic fatigue. The findings allow for a set of recommendations to cruise companies and policymakers for post-COVID-19 cruise industry management.